PeerJ Materials Science 2020
DOI: 10.7717/peerj-matsci.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alkali treatment on the mechanical and thermal properties of sisal/cattail polyester commingled composites

Abstract: Environmental and energy conservation pressure has led to a dramatic increase in the need for economically feasible lightweight materials that can be better substitutes for non-biodegradable materials in reinforced composites. In this study, the mechanical and thermal properties of polyester resin composites hybridized with a blend of untreated and alkali treated sisal (Agave sisalana) and cattail (Typha angustifolia) fibers were evaluated. Composites were fabricated by a hand lay-up technique at an optimal hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…us, the current study augments previous studies which indicated that hybridization of natural fibres in polymer composites improves the mechanical properties of the resultant composites [9,17,31,36,37].…”
Section: Impact Strength At a Constant Fibre Weight Fraction Of 20% Andsupporting
confidence: 82%
See 3 more Smart Citations
“…us, the current study augments previous studies which indicated that hybridization of natural fibres in polymer composites improves the mechanical properties of the resultant composites [9,17,31,36,37].…”
Section: Impact Strength At a Constant Fibre Weight Fraction Of 20% Andsupporting
confidence: 82%
“…Flexural, tensile, and compressive strengths of cattail/ polyester composites were much lower compared with sisal/ polyester composites. is trend can be explained by the fact that tensile properties of sisal fibres are higher than those of cattail fibres and thus implying that the reinforcing effect of sisal fibres in the matrix is better than that of cattail fibres (Figure 8) [17]. It was also noted that the diameter of the sisal fibre was less than that of the cattail fibre, and therefore, the surface area of the fibre exposed to the matrix is higher in sisal/polyester composites than in cattail/polyester composites [17,29,30].…”
Section: Flexural Tensile and Compressive Strengths Of Hybridmentioning
confidence: 99%
See 2 more Smart Citations
“…Edhirej et al reported that TPS composites reinforced with untreated bagasse with size of < 300 m exhibited higher tensile strength compared with those reinforced with bagasse sized within 300-600 m [6]. TPS/RH1 and TPS/treated RH1 composites showed similar levels of elongation at break (Figure 8 alkaline treatment points to more effective fiber/matrix load transfer [56,57] as a result of stronger interfacial interactions arising from favorable topological and wetting contributions [58][59][60]. In principle, interface bonding in fiber reinforced composites takes place via electrostatic forces, chemical bonding and mechanical interlocking mechanisms [61].…”
Section: Mechanical Propertiesmentioning
confidence: 96%